2014
DOI: 10.1108/ijcthr-08-2014-0071
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation and tourism: holy grail or emperor’s robes?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 71 publications
3
31
0
Order By: Relevance
“…Based on these outcomes, more practical suggestions for changes to the design of activities and interpretation to improve environmental learning are provided in Section 6.5. While previous research has shown that conservation messages are an important component of a wildlife tourism experience , the effectiveness of conservation messages in interpretation has received little attention (Moscardo, 2014). More than half of the visitors in this study did not recall a single conservation message, a finding in common with previous research (Schultz & Joordens, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Based on these outcomes, more practical suggestions for changes to the design of activities and interpretation to improve environmental learning are provided in Section 6.5. While previous research has shown that conservation messages are an important component of a wildlife tourism experience , the effectiveness of conservation messages in interpretation has received little attention (Moscardo, 2014). More than half of the visitors in this study did not recall a single conservation message, a finding in common with previous research (Schultz & Joordens, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…It can also be used to reduce the negative impacts of visitors often associated with leisure settings (banging on glass, flash photography, feeding animals or other actions that may impact on animals) and encourage voluntary compliance. However, despite widespread acceptance of the value of interpretation in tourism, there remain questions about the nature and effectiveness of interpretation as a tourism management tool (Moscardo, 2014).…”
Section: Reaching the Zoo Or Aquarium Visitormentioning
confidence: 99%
“…Underlying most such applications, however, is a focus on communication of knowledge to, and education of, the nonspecialist public (Staiff 2014). Moscardo effectively captures this focus in her review of the practice: “Heritage interpretation is defined as persuasive communication activities, such as guided tours, brochures and information provided on signs and in exhibitions, aimed at presenting and explaining aspects of the natural and cultural heritage of a tourist destination to visitors” (2014:462).…”
Section: What Is Heritage Interpretation?mentioning
confidence: 99%
“…Interpretation Australia (2014) regarded heritage interpretation as a communication between thoughts and feelings to help people know more about themselves and the environment where they live. The British Association for Heritage Interpretation (2014) viewed that interpretation enriches people's life through motivating their emotion, enhancing their experience, deepening their understanding of places, folks, and events as well as objects [7]. Based on what is mentioned above, it can be concluded that the words frequently mentioned in the definitions of interpretation are education, communication, information, interpretation, meaning, understanding et al …”
Section: The Development Of Environmental Interpretation Definitionmentioning
confidence: 99%